2014
DOI: 10.1007/s13277-014-2206-4
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26a inhibits prostate cancer progression by repression of Wnt5a

Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that are involved in different biological processes by suppressing target gene expression. miRNA microarray analysis revealed a significant decrease of miR-26a in prostate cancer tissues versus their normal counterparts, but the role of miR-26a is needed to investigate. In the present study, we found that miR-26a expression was lower in prostate cancer tissues compared with their normal controls, so did the prostate cancer cells. Next, by lentivirus-mediated gain-of-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 25 publications
4
33
0
Order By: Relevance
“…Although miR-26a and HMGA1 were selected from statistical analysis, further analyses confirmed that these molecules affected the migration, invasion and growth properties of a human adenocarcinoma cell line. These results were consistent with previous studies, in which miR-26a was identified as a tumor suppressor (14,15) and HMGA1 as an oncoprotein (16) in various cell types. Accordingly, a combined approach, which evaluates cell lines using miRNA-seq may assist in identifying miRNAs, which are biologically relevant in particular cancer cell types.…”
Section: Discussionsupporting
confidence: 94%
“…Although miR-26a and HMGA1 were selected from statistical analysis, further analyses confirmed that these molecules affected the migration, invasion and growth properties of a human adenocarcinoma cell line. These results were consistent with previous studies, in which miR-26a was identified as a tumor suppressor (14,15) and HMGA1 as an oncoprotein (16) in various cell types. Accordingly, a combined approach, which evaluates cell lines using miRNA-seq may assist in identifying miRNAs, which are biologically relevant in particular cancer cell types.…”
Section: Discussionsupporting
confidence: 94%
“…The tumor-suppressive properties of miR-26 family have been widely reported for many cancers, such action being exerted via targeting of several oncogenes. For miR-26a, targeting of HMGA1 has been documented for bladder cancer,42 and targeting of HMGA2 for gallbladder cancer,43 targeting of FGF9 for gastric cancer,44 targeting of CKS2 for papillary thyroid carcinoma,45 targeting of NRAS and E2F2 for gastric cancer,46 and targeting of Wnt5a for PCa have been documented,47 while for miR-26b, targeting of COX-2 for lung cancer,48 EphA2 for glioma,49 USP9X for hepatocellular carcinoma,50 MIEN1 for non-small-cell lung cancer,51 and ULK2 for PCa52 have been documented. In PCa, both miR-26a and miR-26b target La-related protein 1 53.…”
Section: Discussionmentioning
confidence: 99%
“…Mature miRNAs can specifically bind to the 3'-untranslated regions (3'-UTRs) of target cellular mRNA, in turn triggering mRNA degradation or inhibition of translation (9). A previous study has reported that miRNA-26a (miR-26a) had decreased expression in prostate cancer (10). However, there is limited knowledge about the role of miR-26a in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%